Analis Warisan Terbuka Menurut BW (Burgelijk Woetbook) Dan Hukum Islam - Nur Faizza; Muhammad Saputra; Muhammad Al-Mansur (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Civil law (Burgerlijk wetboek) is a part of Indonesian law that can be used as a guideline in dividing inherited assets. In the sense that inheritance is open according to the Civil Code, namely in Article 830 inheritance is only opened after death, which means it can only be distributed if one of the heirs has died. This contains the problem of an heir distributing the inheritance while he is still alive without waiting for an event (the death of the heir). If we investigate this, it will open up a new law or a new process, not much different from Islamic inheritance law, both of which are the same as waiting for death. The purpose of this research is to analyze how inheritance occurs according to the Civil Code of the Civil Code. The method used by the author is a qualitative method which pays attention to empirical data with library research. Based on this, it is contained in the basic things about the emergence of heirs that occur when one person dies. However, if someone distributes it first, it is called a gift or will.